The Description Of Family Caregiver Knowledge Levels On Post-Hospitalization Stroke - Imas Hayyuningtyas Kurniasih; Lalu M. Panji Azali; Diyanah Syolihan Rinjani Putri; Yunus (Indonesian Journal Publisher, 2025)
Stroke is a non-communicable disease with serious health issues, ranking as the third leading cause of death worldwide and the primary cause of physical disability. Family knowledge about stroke is crucial because the family's understanding influences preventive behavior against stroke attacks through lifestyle changes. A lack of knowledge about stroke can lead to delays in seeking treatment during an attack, depression, and unpreparedness in caring for the patient. These factors contribute to the severity of the patient's condition, recurrent stroke attacks, paralysis, and even death. This study aims to determine the level of knowledge among family caregivers about post-hospitalization stroke in the neurology clinic of Dr. Moewardi General Hospital, Surakarta. This research uses a quantitative method with a descriptive approach. The sampling technique applied purposive sampling with a total of 45 respondents. The instrument used was a questionnaire to measure caregivers' knowledge about stroke. The collected data were then analyzed using descriptive statistics. The results showed the level of knowledge among family caregivers about stroke: 9 respondents (20.0%) had good knowledge, 20 respondents (44.4%) had moderate knowledge, and 16 respondents (35.6%) had poor knowledge. From these findings, it can be concluded that family caregivers of stroke patients have a moderate level of knowledge about stroke.